Random-Track: The End of the Academic Career As We Know It? (Higher Education Politics and Economics, 2025)
The decrease in public funding and the subsequent increase in temporary employment in academia are often viewed as crisis symptoms. While the crisis rhetoric may be premature, the turn towards hyper-competitive qualification systems that generate unfixed career advancement models may indeed mark a break from the tenure-oriented career structure. Drawing on a pilot online survey conducted with over 300 academics within the European Research Area (ERA), this study reveals a potentially radical transformation of the academic career paradigm from a tenure-oriented path towards an increasingly episodic, nomadic, and unsystematic drift, defined here as ‘random-track’.